2014
DOI: 10.4238/2014.october.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bovine SMO gene polymorphisms on the body measurement and meat quality traits of Qinchuan cattle

Abstract: ABSTRACT. Beef cattle breeding programs focus on improving important economic traits, including growth rates, and meat quantity and quality. Molecular marker-assisted selection based on genetic variation represents a potential method for breeding genetically improved livestock with better economic traits. Smoothened (SMO) protein is a signal transducer that contributes to the regulation of both osteogenesis and adipogenesis through the hedgehog pathway. In this study, we detected polymorphisms in the bovine SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…This phenomenon may be explained by the three possible reasons. First, the number of specific genotypes (AG of SNP2 and CC of SNP3) was too small probable due to genetic drift [24]. Second, the economically favorable traits (such as low average wool fiber diameter) have been artificially selected and SNPs 2 and 3 as the beneficial SNPs or in linkage equilibrium with the beneficial SNPs might have been accumulated [25].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be explained by the three possible reasons. First, the number of specific genotypes (AG of SNP2 and CC of SNP3) was too small probable due to genetic drift [24]. Second, the economically favorable traits (such as low average wool fiber diameter) have been artificially selected and SNPs 2 and 3 as the beneficial SNPs or in linkage equilibrium with the beneficial SNPs might have been accumulated [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a total of 11 SNPs were identified in ovine DKK1 genomic region. From these 11 identified SNPs, six SNPs (SNPs2 to 5, 10, 11) were not in the Hardy-Weinberg equilibrium, which may be explained by the following reasons: (1) the alleles may be the predominant alleles during genetic evolution, thus being more conserved and more common than other alleles in this population [ 35 ]; (2) The number of sheep examined in each strain was not large enough that genetic drift makes a significant force [ 36 ]; (3) The alleles may be tightly linked with an advantageous allele; (4) The economically favorable traits were artificially selected [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…When incubated with the restriction enzyme, Sau96I, to detect the G > C mutation observed at the 21,234 bp-locus in Qinchuan cattle, the PCR product produced three banding patterns representing CC, GC, and GG ( Figure 1 and Figure 2). Commensurate with the result of [7], the CC is represented by one fragment (163 bp), GG by two fragments (64 and 99 bp), and GC by three fragments (64, 99 and 163 bp).…”
Section: Smo Exonmentioning
confidence: 88%
“…The two SNP-C22424T and C22481T-reported by Zhang et al [7] that caused synonymous substitution of glycine and histidine, respectively, were identified. The software allowed identification of homozygous and heterozygous genotype carriers.…”
Section: Smo Exon 11mentioning
confidence: 91%
See 1 more Smart Citation